New records of the caridean shrimp genus Processa Leach, 1815 (Crustacea: Decapoda: Processidae) from Japan, with descriptions of two new species - Komai, Tomoyuki; Fujita, Yoshihisa (Zootaxa, 2014)
Three species of the processid shrimp genus Processa Leach, 1815, including two new species, are reported from shallow coastal waters in Okinawa Island, Ryukyu Islands, Japan: P. affinis Hayashi, 1975, P. filipes n. sp. and P. hayashii n. sp. The present specimens of P. affinis represent the rediscovery and range extension of this poorly known species, originally described from Indonesia. Male characteristics of P. affinis are documented for the first time. The two new species are referred to the P. aequimana Paulson, 1875 species group. Processa filipes n. sp. is characteristic in the greatly elongate fifth pereopod and the transverse ridge on thoracic sternite 8 consisting of soft cuticle. Processa hayashii n. sp. is characterized by the presence of a deep concavity on the anterolateral margin of the carapace just inferior to the antennal tooth. The number of species of Processa known from Japanese waters is raised from five to eight.